Contribución al conocimiento de las larvas de Ololygon fuscovaria (Lutz, 1925) (Anura: hilydae) : I. Distribución de los queratodontos - Montanelli, Silvana B. (1992)
The study of the labial teeth row distribution of 142 Ololygon fuscovaria larvae showed that it can be found two dental formulae a: 1,1-1/1-1.2 and b: 1,1-1/3. The P-1 row could have variations on b distribution, but they do not modify the formula that the tadpole gots during the premetamorphosis stages.